Cinco mulheres: vozes em ricochete - Ivete Lara Camargos Walty (Estudos de Literatura Brasileira Contemporânea)
Marcelino Freire, whose character moves between the countryside and the city, has been writing as one who hears the others, exercising alterity. Taking as a start- ing point the texts’ enunciation and inscenation dynamics, this work aims to fol- low the path of five poor women, “Muribeca”, “Comadre”, “Darluz”, “Da Paz” and “Totonha”, pointing to the tension exposed between the social voices pre- sented and the author ́s voice. The latter comes as the result of strategies used in the composing of an explicitly interlocutory writing, which includes the reader.